2005
DOI: 10.2527/2005.831208x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic corticosteroid-binding globulin (CBG) messenger RNA expression and plasma CBG concentrations in young pigs in response to heat and social stress1,2

Abstract: Plasma cortisol, porcine corticosteroid-binding globulin (pCBG), hepatic CBG expression, and other physiological and behavioral measures of stress were studied in pigs in response to elevated temperature in conjunction with establishing a social hierarchy. Twenty-four crossbred pigs were weaned at 25 d of age (three or six pigs from six sows) and housed in littermate groups at 23 +/- 2 degrees C. At 57 d of age (d 0), animals were weighed and placed under general anesthesia for collection of blood (10 mL) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 42 publications
3
25
1
Order By: Relevance
“…Apart from immune stimuli, haptoglobin can also be released in response to other stressors like hot ambient temperature (Heo et al, 2005), transport (Piñeiro et al, 2007b) or unpredictable feeding practices (Piñeiro et al, 2007a). In the present study, haptoglobin levels were unrelated to cortisol levels.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Apart from immune stimuli, haptoglobin can also be released in response to other stressors like hot ambient temperature (Heo et al, 2005), transport (Piñeiro et al, 2007b) or unpredictable feeding practices (Piñeiro et al, 2007a). In the present study, haptoglobin levels were unrelated to cortisol levels.…”
Section: Discussionmentioning
confidence: 43%
“…It is noteworthy that CBG, which is a protein of hepatic origin like positive and negative acute phase proteins, displays reduced concentrations in cases of inflammatory conditions (Garrel, 1996), and thus varies in the opposite way to haptoglobin. These opposite variations have also been observed in pigs, in inflammatory (Carroll et al, 2003) as well as in other stressful conditions (Heo et al, 2005;Piñeiro et al, 2007a and2007b).…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, it is assumed that the decrease of CBG levels in newborn piglets may result from direct inhibition of fetal hepatitic CBG biosynthesis by elevated maternal cortisol exposure during both mid-and late gestation. This decrease in CBG and the unchanged total cortisol levels indicate a higher amount of biologically available free cortisol, which is also found in animals under conditions of chronic stress (Kim et al 1999, Stefanski 2000, Heo et al 2005.…”
Section: Discussionmentioning
confidence: 66%
“…Conversely, some studies have reported a decrease in plasma concentration of cortisol in pigs exposed to hot conditions. Heo et al (2005) observed low circulating levels of cortisol in 20-30 kg BW pigs exposed to 32 °C. In addition, Kim et al (2009) reported that cortisol levels were 22% lower in growing pigs exposed to 40 °C when compared with pigs kept at 24 °C.…”
Section: Neuroendocrine Adjustmentsmentioning
confidence: 77%